2003
DOI: 10.1016/j.jpainsymman.2003.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue after treatment for malignant and benign bone and soft tissue tumors

Abstract: Fatigue has been mentioned as an important complaint in several groups of disease-free patients after curative treatment for cancer. However, it has never been investigated in a sample of patients who have been treated for a bone or soft tissue tumor in the past. In the current study, these patients participated. Measurement included posted questionnaires at baseline and at follow-up (two years later). Baseline results indicated that fatigue is a severe problem for 28% of the investigated patients. Percentages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
4
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 29 publications
0
71
4
15
Order By: Relevance
“…10,11 Furthermore, it seems that patients with more aggressive treatments are more at risk for persistent fatigue. [12][13][14] However, little is known about the aetiology of persistent fatigue and at this moment, persistent fatigue is unexplainable by somatic factors. Fatigue seems to be elicited during the treatment phase, but later on there is no clear relationship between persistent fatigue and initial disease and cancer treatment variables.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Furthermore, it seems that patients with more aggressive treatments are more at risk for persistent fatigue. [12][13][14] However, little is known about the aetiology of persistent fatigue and at this moment, persistent fatigue is unexplainable by somatic factors. Fatigue seems to be elicited during the treatment phase, but later on there is no clear relationship between persistent fatigue and initial disease and cancer treatment variables.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption is that cancer itself and/or cancer treatment may have triggered fatigue (precipitating factors), but other factors are responsible for the persistence of fatigue complaints (perpetuating factors). 13,18,19 In a previous study, we found cognitive behaviour therapy (CBT) especially designed for fatigued cancer survivors effective in reducing fatigue and impairment. 18 The rationale of this intervention was based on the model of precipitating and perpetuating factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue seems to persist even after the "cure" of cancer, since 19% to 58% of treated people without evidence of cancer reported the symptom (5)(6) .…”
mentioning
confidence: 99%
“…In the same manner, performance status was worse among fatigued than among nonfatigued subjects. Various studies in different scenarios also identified performance status, pain, depression and sleep alteration, among others, as factors related to fatigue (4,6,11,14) .…”
mentioning
confidence: 99%